Public Choice - Mixon, Franklin G. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Interest in politics and the political process—topics that economists consider to be the purview of the sub-field of study known as public choice—appears to be as high as ever. This Special Issue aims to provide a collection of high-quality studies covering many of the varied topics traditionally investigated in the growing field of public choice economics. These include expressive and instrumental voting, checks and balances in the enforcement of rules, electoral disproportionality, foreign aid and political freedom, voting cycles, (in)stability of political ideology, federal spending on environmental goods, pork-barrel and general appropriations spending, politics and taxpayer funding for professional sports arenas, and political scandal and “friends-and-neighbors” voting in general elections. In bringing these topics together in one place, this Special Issue offers a mix of conceptual/formal and empirical studies in public choice economics.